Anti-tumor activity of all-trans retinoic acid in gastric-cancer: gene-networks and molecular mechanisms - Luca Guarrera; Mami Kurosaki; Silvio-Ken Garattini; Maurizio Gianni’; Gianpiero Fasola; Luca Rossit; Michele Prisciandaro; Maria Di Bartolomeo; Marco Bolis; Paola Rizzo; Claudia Nastasi; Marika Foglia; et al. (Journal of Experimental & Clinical Cancer Research, 2023)
Abstract Background Gastric-cancer is a heterogeneous type of neoplastic disease and it lacks appropriate therapeutic options. There is an urgent need for the development of innovative pharmacological strategies, particularly in consideration of the potential stratified/personalized treatment of this tumor. All-Trans Retinoic-acid (ATRA) is one of the active metabolites of vitamin-A. This natural compound is the first example of clinically approved cyto-differentiating agent, being used in the treatment of acute promyelocytic leukemia. ATRA may have significant therapeutic potential also in the context of solid tumors, including gastric-cancer. The present study provides pre-clinical evidence supporting the use of ATRA in the treatment of gastric-cancer using high-throughput approaches. Methods We evaluated the anti-proliferative action of ATRA in 27 gastric-cancer cell-lines and tissue-slice cultures from 13 gastric-cancer patients. We performed RNA-sequencing studies in 13 cell-lines exposed to ATRA. We used these and the gastric-cancer RNA-sequencing data of the TCGA/CCLE datasets to conduct multiple computational analyses. Results Profiling of our large panel of gastric-cancer cell-lines for their quantitative response to the anti-proliferative effects of ATRA indicate that approximately half of the cell-lines are characterized by sensitivity to the retinoid. The constitutive transcriptomic profiles of these cell-lines permitted the construction of a model consisting of 42 genes, whose expression correlates with ATRA-sensitivity.  The model predicts that 45% of the TCGA gastric-cancers are sensitive to ATRA. RNA-sequencing studies performed in retinoid-treated gastric-cancer cell-lines provide insights into the gene-networks underlying ATRA anti-tumor activity. In addition, our data demonstrate that ATRA exerts significant immune-modulatory effects, which seem to be largely controlled by IRF1 up-regulation. Finally, we provide evidence of a feed-back loop between IRF1 and DHRS3, another gene which is up-regulated by ATRA. Conclusions ATRA is endowed with significant therapeutic potential in the stratified/personalized treatment gastric-cancer. Our data represent the fundaments for the design of clinical trials focusing on the use of ATRA in the personalized treatment of this heterogeneous tumor. Our gene-expression model will permit the development of a predictive tool for the selection of ATRA-sensitive gastric-cancer patients. The immune-regulatory responses activated by ATRA suggest that the retinoid and immune-checkpoint inhibitors constitute rational combinations for the management of gastric-cancer.